Quantifying E. coli O157:H7 via linear sweep voltammetry in phosphate buffered saline and tap water - Ali Ahmed, Nasteho; Ramli, Nurul Izzati; Abdul Jalal, Nurfatin Azma; Abd. Wahab, Mohd. Firdaus; Wan Salim, Wan Wardatul Amani (Kulliyyah of Engineering International Islamic University Malaysia, 2018)
E. coli O157:H7 is a common microorganism that is responsible for contaminating water after major floods events. Standard methods of pathogen detection cannot be utilized in the field; the need for a portable immunosensor becomes urgent so detection of pathogens can be done at remote post-flood areas with no lab and technician access. In this study, the objectives are to analyze E. coli binding to reduced graphene oxide (rGO) electrode surfaces via Linear Sweep Voltammetry (LSV) in phosphate buffered saline (PBS), pH 7.4, and potable tap water, and to correlate voltammetry results with E. coli attachment on electrodes by using FESEM. From the results, LSV in PBS shows sensitivity of 38.7 µA/(cell/ml) in comparison to tap water, with a lower sensitivity of 2.20 µA/(cell/ml). Linear range from 103 to 108 cells/µl was achieved in both solution types. FESEM results show higher attachment of cells on rGO-based electrodes for higher concentration of cells, confirming the lowering of current in LSV measurements owing to increased cell attachment.